Global Competitive Strategy - Gould, Anthony M. (Relations industrielles / Industrial Relations, 2008)
Global Competitive Strategy, by Daniel F. Spulber, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Competitive advantage; Corporate planning; Executives; Globalization; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z